Opportunities and Challenges for Microbial Synthesis of Fatty Acid-Derived Chemicals (FACs) - Liu, Yilan; Benitez, Mauricio Garcia; Chen, Jinjin; Harrison, Emma; Khusnutdinova, Anna N.; Mahadevan, Radhakrishnan (Frontiers in Bioengineering and Biotechnology, 2021)
Global warming and uneven distribution of fossil fuels worldwide concerns have spurred the development of alternative, renewable, sustainable, and environmentally friendly resources. From an engineering perspective, biosynthesis of fatty acid-derived chemicals (FACs) is an attractive and promising solution to produce chemicals from abundant renewable feedstocks and carbon dioxide in microbial chassis. However, several factors limit the viability of this process. This review first summarizes the types of FACs and their widely applications. Next, we take a deep look into the microbial platform to produce FACs, give an outlook for the platform development. Then we discuss the bottlenecks in metabolic pathways and supply possible solutions correspondingly. Finally, we highlight the most recent advances in the fast-growing model-based strain design for FACs biosynthesis.